Removal Of Paracetamol And Tetracycline From Synthetic Wastewater Using Heterogeneous Tio2 Solar Photocatalyst - Lee, Chee Mei (2017)
Paracetamol and tetracycline are well known with tremendous annual worldwide production and high global consumption rate. Their occurrence in the various water compartments has been reported in different countries. In this study, sewage characterization showed that the conventional wastewater treatment plant was effective to degrade the conventional parameters to the acceptable conditions, but it was unable to remove the pharmaceutical compounds (paracetamol and tetracycline) appeared in the sewage treatment plant (STP). Next, this study investigated the performance of heterogeneous photocatalysis titanium dioxide [TiO2]/solar treatment process in removing the paracetamol and tetracycline individually from the synthetic wastewater. In the batch study, the effects of the selected variables (sunlight exposure period, pH, TiO2 concentration and initial concentration of pharmaceutical) on the photocatalytic degradation efficiencies of paracetamol and tetracycline were investigated by using the single-variable-at-a-time (SVAT) method. Results showed that all of these selected factors greatly affected the removal efficiencies of paracetamol and tetracycline. Next, central composite design (CCD) based on the response surface methodology (RSM) were used to optimize the TiO2 and pharmaceutical concentrations. Under the optimum conditions of 1.0 g/L of TiO2 concentration and 0.06 g/L of initial concentration of paracetamol, around 82% of paracetamol removal efficiency was attained, whereby, approximately 75% of tetracycline removal efficiency was achieved under the optimum conditions of 2.64 g/L of TiO2 concentration and 0.07 g/L of initial concentration of tetracycline. Finally, the kinetic of the photocatalytic degradation of paracetamol and tetracycline fitted well with the Langmuir-Hinshelwood kinetic model. The reaction rate constant (k) and adsorption constant (K) for the photocatalytic degradation process of paracetamol and tetracycline were 0.00052 g/L.min, 131.58 L/g and 0.0028 g/L.min, 71.43 L/g, respectively. The results from these in situ experiments have proven the reliability of the solar in the photocatalysis treatment process.